STUDY OF MODERN TROPICAL ARCHITECTURAL DESIGN CONCEPT IN VERTICAL RESIDENCE - Saliim, Alief Muzakkii; Satwikasari, Anggana Fitri (Border: Jurnal Arsitektur, 2022)
Indonesia is a country with a wet tropical climate with high rainfall intensity and short dry season. Indonesia is also one of the archipelagic countries which is quite densely populated, this density makes the demand for residential housing increasing every year. The solution to overcome these problems is to create vertical residences, or commonly referred to as flats, apartments, and condominiums. However, with the tropical climate conditions in Indonesia, vertical housing has more challenges in overcoming the problem of residential temperature due to areas that are more exposed to the sun. Therefore, this study aims to examine the quality of the vertical occupancy of Kampung Akuarium Flats against tropical climatic conditions. This research method is carried out by describing the condition of the building against the parameters of a tropical climate-based dwelling. The results of the study show that the design applied has climatic factors and can meet the needs of residential density in Indonesia.